Implementation of character education in Dasa Darma of Scouts and Hizbulwathan Boys Scout Laws - Ana Zulfaturrohmawati (ATTARBIYAH: Journal of Islamic Culture and Education, 2017)
This research is based on the importance of implanting of the character education of students as the provision of life in the society, leads the students to develop the potential of students have with the values contained in dasa darma of scout and Hizbul Wathan Boys Scout Laws. The aim of this study is to find the implementation of character education, and the similarities dimensions and the differences implementation of character education in the Dasa Darma of Scout and the Boys Scout Laws of Hizbul Wathan. This research uses qualitative methods. Based on the results of the scout activities using team systems, adult member partnerships in activities and separate unit systems, and coaches provide role models to Scout members. Hizbul Wathan scouting is the practice of Islamic aqidah, the formation and guidance of noble morals according to Islamic teachings. Implementation equation in character education in Dasa Darma of Scout and Hizbul Wathan Boys Scout laws (1) aspect of goal to inculcate the value of positive character, (2) habituation and practice, giving exemplary one, creation of a pleasant milieu of character (3) internalization of positive values inculcated by all the citizens of the school. While the difference is (1) the scout honor code is dasa darma, whereas Hizbul Wathan is the boys scout laws, (2) scouting is universal, while Hizbul Wathan is national, and (3) scouting fill knowledge, mental stability, skills, experiences, social, spiritual, and emotional feelings, while Hizbul Wathan on Islam religion and scouting skills.